2015
DOI: 10.1186/s12889-015-1514-y
|View full text |Cite
|
Sign up to set email alerts
|

The humanistic, economic and societal burden of Herpes Zoster in Europe: a critical review

Abstract: BackgroundHerpes zoster (HZ) or “shingles” is common in persons aged 50 years or over. HZ is characterised by a painful dermatological rash which typically resolves in approximately one month. Persistent pain for months or years after rash onset, however, is a common complication of HZ; referred to as post-herpetic neuralgia (PHN). Both HZ and PHN have a significant impact on patients’ lives, with considerable implications for healthcare systems and wider society. The aim of the present review is to provide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 78 publications
3
51
2
Order By: Relevance
“…25 Due to this lack of a consensus definition and the varying age ranges of the populations being studied, the incidence of PHN after HZ ranges from 5–30% and occurs in 50% of HZ affected individuals greater than 85 years. 2, 3, 5, 2628 It is considered the most debilitating sequelae of HZ since it impairs the affected individual’s quality of life across all 4 health domains: physical, psychological, functional and social. 27 …”
Section: Post-zoster Sequelaementioning
confidence: 99%
“…25 Due to this lack of a consensus definition and the varying age ranges of the populations being studied, the incidence of PHN after HZ ranges from 5–30% and occurs in 50% of HZ affected individuals greater than 85 years. 2, 3, 5, 2628 It is considered the most debilitating sequelae of HZ since it impairs the affected individual’s quality of life across all 4 health domains: physical, psychological, functional and social. 27 …”
Section: Post-zoster Sequelaementioning
confidence: 99%
“…HZ and PHN have major impacts on patients’ lives [29] and constitute a significant economic burden for health care systems and societies at large [30]. A treatment that effectively prevents PHN in patients at high risk could improve the quality of life of patients with HZ and also reduce health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 50% of patients with HZ and up to 81% of patients with PHN report a negative impact on their social and familiar relationships. 13,14 Several studies have shown that pain and other physical and psychological symptoms associated to HZ and PHN can significantly affect the productivity and working capacity of the affected population. 15 About 75% and 66% of subjects with HZ infection report a decrease of their concentration and work ability, and stopped working, respectively.…”
Section: Introductionmentioning
confidence: 99%